HUBUNGAN KONSEP DIRI DENGAN RESILIENSI ANAK DI PANTI ASUHAN AL-ANSHOR KECAMATAN TENAYAN RAYA KOTA PEKANBARU - Karmilawati Karmilawati; Ria Novianti; Hukmi Hukmi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: this research aims to know the relationship of self concept by resiliensi children in Orphanages, Al-Raya Tenayan Distric Anshor Pekanbaru. As for the populas in this study are all the children of the orphanage Al-4-6 year-old Anshor totalling 39 children, the sample of this research as much as 39 children using the technique of sampling is saturated. Methods used i.e. correlation Pearson Product Moment to see the relationship between the concept of self variables with resiliensi children. Techniques of data collection, namely the observation sheet using the Likert Scale. Data analysis techniques using test scale and the analysis of statistical methods with the SPSS program for Windows ver. 23. Based on the hypothesis test is obtained there is significant and positive relationship between the child's self concept by resiliensi children in Orphanages, Al-Raya Tenayan Distric Anshor Pekanbaru. It is known from the value of the koefesien correlation of rxy = 0.485 and significant degrees of 0.002 < 0.05. the level of the relationship between the concept of yourself with resiliensi children are included in the value of the resulting determination of koefesien 23.5%, meaning that the concept of self giving influence of 23.5% against reseliensi.Keywords: Self Concept, Resiliensi